De novo biosynthesis of taxifolin in yeast peroxisomes - Qi Wu; Ruibing Chen; Lei Zhang (Microbial Cell Factories)
Abstract Background Yeast peroxisomes have been engineered as ideal synthetic compartments to enhance the heterologous biosynthesis of natural products, particularly terpenoids and fatty acid derivatives. This advantage is primarily attributed to the rich acetyl-CoA pool generated from the spatially specific fatty acid β-oxidation within peroxisomes. However, their potential for flavonoid biosynthesis has been largely underexplored, primarily due to limited knowledge regarding precursor transport, cofactor availability, and the redox environment in peroxisomes. Results In this study, we successfully compartmentalized the biosynthesis of taxifolin, a dihydroflavonol, in Saccharomyces cerevisiae peroxisomes. The result indicated that flavonoid biosynthesis in peroxisome offers a more efficient approach compared to its synthesis in the cytosol. This study managed to expand the application scope of peroxisome compartmentalization to flavonoid biosynthesis. By reinforcing the rate-limiting steps, optimizing cofactor supply and activation of fatty acids, we accomplished the de novo synthesis of taxifolin in peroxisomes for the first time, attaining a titer of 120.3 ± 2.4 mg/L in shake-flask fermentation using a minimal medium. Conclusion These findings highlight the feasibility of peroxisomal compartmentalization for flavonoid biosynthesis, providing new insights and a framework for the biosynthesis of other high-value flavonoids using yeast peroxisomes.